Application of Knowledge Sharing Features Using the algorithm Boyer-moore On Knowledge Management System (KMS) (Case Study: Department of Communication and Information Government Prabumulih) - Devi Renista Candra; Ken Ditha Thania (Jurnal Sistem Informasi, 2017)
Abstract Department of Communication and Information Technology Government Prabumulih is a device which acts as a local government responsible for the fields of transportation, communication and informatics at level Prabumulih. The Department has the tacit and explicit knowledge that has not been optimally managed and documented. Office requires a knowledge management system, as evidenced by knowledge sharing features. System development method used is the 10-step knowledge management roadmap by Amrit Tiwana . While the method of knowledge sharing using the Boyer-Moore algorithm. The results of this study are worth a Knowledge Management System applied to the department. And based on the results of testing the application of knowledge sharing feature using the Boyer-Moore algorithm is very effective. Â  Keywords: Knowledge Management System, Knowledge Sharing, Boyer-Moore Algorithm